Exploring medication non-adherence among patients with Diabetes Mellitus - Abdullah, Nor Fadhilah; Cheong, Ai Theng; Sowtali, Siti Noorkhairina; Lee, Khuan (Fakultas Keperawatan Universitas Andalas, 2019)
The prevalence of diabetes mellitus (DM) is steadily increasing worldwide, with a significant DM population in Asian countries. Adherence towards medications is important for achieving good glycaemic control among patients with DM. Thus, patient medication-adherence problem should be identified to optimise DM management. This study assessed medication adherence among patients with type 2 diabetes and explored reasons of non-adherence. An exploratory sequential of mixed method was used. The first phase was a cross-sectional study using Medication Compliance Questionnaire (MCQ) to identify non-adherence patient. The second phase followed by semi-structured interviews among 12 purposely selected non-adherence patients. This study was done at two public hospitals at West Malaysia. 399 patients participated in the first phase of the study and 46.6% of the patients were non-adherence. Factors of non-adherence were associated with Malay race (OR 1.66, 95% CI (1.09 2.51), being single (OR 1.79, 95% CI 1.05, 3.05) and has poor HbA1c ( OR 2.57, 95% CI 1.61 4.10). The reason of non-adherence were ocncern about medication safety and efficacy, the used of complementary and alternative medicine, poor healthcare providers-patient communication, lifestyle restraint, andemotional vulnerabilityin taking medication. Non adherence issues from the diabetes patient perspective is needed to consider in tackling non-adherence. A patient-centered nursing interventionon non-adherence should be encouraged to improve adherence and maximize patient health outcomes.